CONTRIBUTION OF SOCIAL DEVELOPMENT TASK OUTCOMES TO PEOPLE RELATIONSHIPS - Elsa Gustia; Mudjiran Mudjiran (Jurnal Neo Konseling, 2020)
This study uses a quantitative approach with a descriptive correlational method. The population in this study were all students of class VII SMP Negeri 2 Koto XI Tarusan, totaling 122 students and all grade VIII students at SMP Negeri 2 Koto XI Tarusan, totaling 124 active students in the 2019/2020 school year. The total sample of 152 students obtained through the Stratified Random Sampling technique by administering the linkert model scale. Data were analyzed using descriptive analysis and correlational analysis. Testing the research hypothesis using the Pearson Product Moment correlation formula.The results showed: (1) the average peer relationship was in the good enough category, (2) the average social development of the students was in the medium category, (3) there was a significant contribution between the achievement of social development tasks on friend relationships. peer, while the correlation coefficient is 0.763 and the significance level is 0.000. It can be interpreted that the more contributing to the task of social development, the better the peer relationship.